DIVERSIFIKASI DAN PENANGANAN PASCA PRODUKSI OLAHAN IKAN DI DESA PADANG JAYA BENGKULU UTARA UNTUK MENINGKATKAN NILAI EKONOMI DAN PENDAPATAN MASYARAKAT - Devi Ratnawati; Agus Martono; Hadi Putranto; Devi Rizanty (Universitas Bengkulu, 2017)
The first aim of this activity is giving knowledge to farmer society of fish specially Unit Pengolahan Ikan ( UPI) Melati I in Padang Jaya Village North Bengkulu aboutdiversification of multifarious product which have higher level economic value. Thesecond aim is giving processing practice of some alternative multifarious fish basedproduct to be industrial product which have high economic value. It is also using naturalpickling method, so that it is a good product for healthy life. The practice also givestraining in making safe packaging and product marketing. While, special target is toimprove knowledge of breeder of fish specially Unit Pengolahan Ikan (UPI) Melati I asparticipant of training about diversified multifarious of fish product that having higherlevel economic value and practice some alternative product of fish become multifariouslyof industrial product which have value sell economical, like fish rengginang, cryspy fishbaby and fish of salai. Including handling of after production ie. marketing and packaging.This activity walk better, its product even also have earned to be marketed out of DesaPadang Jaya, ie. Bengkulu town and Jakarta, and become typical pledge present of desa Padang Jaya. Request of this produst even also mount, this matter because of its producthave registering PIRT and get lawful lable so that society feel safe to consuming it.Keywords: Diversification, fish processing, UPI Melati I, Padang Jaya